Hubungan Sikap Spiritual Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII SMP N 1 Ngadirojo Pacitan Tahun Pelajaran 2020/2021 - Arif Wibowo; Fitratul Izza (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
Education has since ancient times been aimed at human beings as a whole and completely covering various aspects. Like one school institution which is precisely at SMP N 1 Ngadirojo. During the initial observation there were several factors that were out of the ordinary of many students who had a less spiritual attitude which was marked by the students 'low awareness of their spiritual attitudes, for example, they chose to play or hang out rather than follow the habituation before class hours (do' a joint and reading a short letter) and the congregation praying dzuhur together. So from this the researcher asks questions about the spiritual attitude of students and is there a relationship between spiritual attitudes towards learning outcomes of Islamic Education. Because of the wide coverage, here it is only focused on examining the relationship of spiritual attitudes to the learning outcomes of PAI class VIII SMP N 1 Ngadirojo in the 2020/2021 school year. This study aims to describe the spiritual attitudes possessed by grade VIII students in Islamic Education subjects and to find out the relationship between spiritual attitudes towards learning outcomes of PAI class VIII SMP N 1 Ngadirojo in the 2020/2021 academic year. To answer this question, the researcher used a quantitative approach. To collect data using interview and questionnaire methods. Here, the interview is used to determine the explanation of the VIII grade PAI field teacher. The questionnaire will be distributed to 57 respondents which is used to determine the spiritual attitudes possessed by students. What will later be linked to the second problem formulation is whether there is a relationship between spiritual attitudes and learning outcomes of Islamic Education. Based on the data analysis, it can be explained that the spiritual attitudes of class VIII students in the PAI subject for the 2020/2021 academic year are in the medium category which is marked by a percentage of 80.7%. To see the relationship of spiritual attitudes to the learning outcomes of PAI class VIII SMP N 1 Ngadirojo here using the SPSS formula where the person correlation test has resulted in data that there is no significant relationship between spiritual attitudes towards learning outcomes of PAI class VIII SMP N 1 Ngadirojo in the 2020/2021 school year which is characterized by a significance value of 0.136 0.05 (distributed with no relationship) and this data is corroborated by rcount rtabel (-0,200 0.261) with no distribution.